2017
DOI: 10.1080/10826084.2017.1404105
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Sexual Relationship Power among Young Women Who Inject Drugs and Their Sexual Partners

Abstract: Background To date, research applying the Sexual Relationship Power Scale (SRPS) has been limited to sexual risk behaviors. Objective We measured levels of sexual relationship power and examined associations between sexual relationship power and injecting and sexual behaviors that place women at increased risk for blood borne infections. Methods Using data from a cross-sectional study of young women who inject drugs (WWID) in San Francisco, USA, logistic regression analysis identified independent associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Women are particularly vulnerable to adverse consequences of identification as a person who injects drugs (such as loss of children, family support and/or sex-work income) and may transition early to injecting into less visible sites such as the groin (Harris and Rhodes, 2013). Gendered power dynamics can exacerbate risk of unsafe injecting, with women more likely than men to have limited control over drug purchase, injection equipment supply, drug injection preparation or administration (Hope et al, 2010;Morris et al, 2018). This can increase the likelihood of receiving injecting assistance and using injecting equipment after others (Wood, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are particularly vulnerable to adverse consequences of identification as a person who injects drugs (such as loss of children, family support and/or sex-work income) and may transition early to injecting into less visible sites such as the groin (Harris and Rhodes, 2013). Gendered power dynamics can exacerbate risk of unsafe injecting, with women more likely than men to have limited control over drug purchase, injection equipment supply, drug injection preparation or administration (Hope et al, 2010;Morris et al, 2018). This can increase the likelihood of receiving injecting assistance and using injecting equipment after others (Wood, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sex work among women is associated with more frequent injecting, and therefore SSTI risk (Kerr et al, 2016). However, as sex work may be undertaken to financially support high levels of injecting (Morris et al, 2018) it is spurious to imply a causal link. The majority of participants in both samples report injecting heroin or a heroin/crack cocaine combination.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have focused on the role of sexual power on injecting behaviors within sexual partnerships [41, 42], our study findings identify injecting-related power in the context of all types of injecting partnerships—not only sexual relationships. Moreover our finding that many interpersonal factors besides power (trust, cooperation, intimacy) play an important role in the way injecting partners perceive risk may explain the null association between the sexual relationship power scale, a quantitative measure of sexual power, and sharing behaviors among a similar sample of injecting partnerships [43]. Cooperation was closely tied to reciprocity related to procuring drugs, preventing overdose and withdrawal, and assisting injecting.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, in the literature, high sexual relationship power indicates a greater ability to communicate sexual preferences, especially in safe sex practices such as condom use and substance use abstinence [ 3 , 8 , 9 , 10 , 11 ]. For example, in a study examining sexual power in Black women, findings suggested that Black women had a greater ability to communicate sexual preferences and negotiate condom use when sexual relationship power was high [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clear linkages have been made between decreased relationship power and increased instances of condom-less sex and substance use, numerous sexual partners, and participation in transactional sex [ 6 , 9 , 10 ]. The trauma of previous relationships often has enduring effects throughout an individual’s life.…”
Section: Introductionmentioning
confidence: 99%